2010
DOI: 10.1097/sla.0b013e3181e462e6
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Cholangiocarcinoma

Abstract: Although recurrence rate represents a frequent problem in ICC, an aggressive approach to recurrence can significantly prolong survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(47 citation statements)
references
References 55 publications
3
43
1
Order By: Relevance
“…The treatment allocation for recurrent ICC is recognized as a significant factor in this study. Radical treatments after recurrence, such as re-resection and ablation, exhibited longterm PRS compared to non-radical treatment for ICC (13.6 vs. 5.3 months), which was consistent with the previous study (19). The capability of radical treatments for recurrent ICC in offering a better chance to eradicate micrometastases generated from the tumor may explain to it (19,30).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The treatment allocation for recurrent ICC is recognized as a significant factor in this study. Radical treatments after recurrence, such as re-resection and ablation, exhibited longterm PRS compared to non-radical treatment for ICC (13.6 vs. 5.3 months), which was consistent with the previous study (19). The capability of radical treatments for recurrent ICC in offering a better chance to eradicate micrometastases generated from the tumor may explain to it (19,30).…”
Section: Discussionsupporting
confidence: 89%
“…The choice of treatment for recurrence was determined from the characteristics of the recurrent tumor, patient preference, and discussion among our multidisciplinary team (MDT) (19)(20)(21). Treatment with curative intent, including surgical re-resection and ablation, was performed in patients with solitary intrahepatic recurrence without a portal vein tumor thrombus, and in patients with an extrahepatic recurrence for which curative treatment was feasible (20)(21)(22).…”
Section: Treatment Of Recurrencementioning
confidence: 99%
“…Considerable interest has been paid to various treatment options against ICC recurrence such as surgical treatment,6, 7, 8 chemotherapy,9 radiation therapy,7 radiofrequency ablation (RFA),10, 11 and transarterial chemotherapy 12, 13 with various degrees of success. In recent reports, aggressive surgical treatment for ICC recurrence led to good patient survival after recurrence, with a 3‐year overall survival (OS) rate of 25%,14 40%,6 and 100% 7.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of N status has also been reported in previous studies. 7,10,11,[37][38][39][40][41][42][43][44] In a recent meta-analysis, LN metastasis was associated with increased risk of death in pool data (HR 2.09), 7 and Kim et al confirmed these findings reporting a similar relative risk of death associated with LN metastasis (HR 2.42; p < 0.001). 12 In the current study, lymph node metastasis (OR 4.64; p = 0.002) was one of the strongest independent predictors of poor prognosis and decreased chance of long-term survival.…”
Section: Discussionmentioning
confidence: 93%